Sustentabilidade da pequena propriedade leiteira - Neto, José Rogério Moura de Almeida; dos Santos, Giancarlo Magalhães; Arroyo, Rafael José Otero; de Sousa, Valesca Oliveira; Ferreira, Ademir de Moraes (Revista Interdisciplinar do Direito - Faculdade de Direito de Valença, 2017)
.